Hybrid Learning Model in Improving Learning Effectiveness in Madrasah - Abdillah; Abd. Qadir Jailani; Mashuri Toha; Bagus Amirulloh; Iskandar Zulkarnain (Penerbit Hellow Pustaka, 2026)
The development of digital technology has encouraged educational institutions, including madrasahs, to adapt learning systems that are more flexible and innovative. One learning approach currently widely applied is the hybrid learning model, which combines face-to-face learning with online learning. This study aims to analyze the implementation of the hybrid learning model in improving learning effectiveness in madrasahs, identify supporting and inhibiting factors, and explain the impact of hybrid learning on student learning outcomes and participation. This research uses a qualitative approach with the type of library research by reviewing various scientific literature, journals, books, and relevant research results related to hybrid learning and Islamic education. Data were analyzed descriptively through data reduction, presentation, and conclusion drawing. The results of the study indicate that the hybrid learning model can improve learning effectiveness in madrasahs through increased flexibility, accessibility, student learning motivation, and more interactive learning processes. However, several obstacles were also found, such as limited internet access, uneven technological mastery among teachers, and inadequate infrastructure. Therefore, collaboration between madrasah institutions, teachers, students, and parents is needed to optimize the implementation of hybrid learning in the future.